Encountering development : the making and unmaking of the Third World - Escobar, Arturo, 1951- (Princeton, N.J. : Princeton University Press, 1995)
"Evaluates development enterprise and development discourse from a critical theory perspective. This view of development policies and control mechanisms employs Colombian case studies of the Programa de Desarrollo Rural Integrado and of the local application of the discourse of women in development"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references (p. [249]-274) and index.
Keywords: Economic development; Economic history -- 1945-; Developing countries -- Economic conditions; Developing countries -- Social conditions